Implementasi Sistem ERP terhadap Kinerja Bisnis: Pendekatan Literatur Review - Alrasyid, Harun; Istianah, Istianah; Marpaung, Zulfina Erita; Indrijawati, Aini; Irdam, Muh (Jurnal Real Riset, 2024)
Information systems are very important factors because they are able to support activities in various business functions within the company and lead to improving company performance. Through the use of information technology, companies can run business processes more effectively and efficiently and can process data more accurately so that it can be better than other companies. Therefore, companies must create and design special systems that can be used to manage and produce information according to company needs. The purpose of this study is to determine the benefits as well as obstacles of ERP implementation. The results found from this literature study are the benefits and barriers in implementing ERP, to facilitate the continuous success of the ERP system and ensure better impact. This study used the Systematic Literature Review method. The number of articles found was 32 articles which were then grouped based on the same concept and discussion as the topic raised. The result of this study is that the implementation of ERP systems affects business performance and has the benefits and problems faced from implementing ERP.